Spider prey (Araneae) of Trpoxlon (Trparilum) rogenhori (Hymenoptera: Sphecidae) in southeastern Brazil - Camillo, Evandro; Brescovit, Antonio D. (Revista de Biología Tropical, 2000)
Fifty five nests and 216 cells of Trpoxlon (Trypargilum) rogenhoferi were obtained from trap-nests (cut bamboo canes) in Santa Carlota Farm (Itaoca Section=IS and Santana Section=SS),Cajuru and on the Sao Paulo University Campus,Ribeirao Preto (=RP),both in the State of Sao Paulo,Brazil (Sept. 199: - Oct. 1995). The prey (spiders) of 40 cells from lS,58 from SS and 39 from RP were identified. The greatest nesting frequency occurred during the hot and wet season (September to April). T rogenhoferi preyed upon individuals of five spider families,with Araneidae (orb-weaver spiders) being the most frequent (99.6%). Alpaid af negr (58%) was the most fquently collected species in lS, followed by A. alto (24.8%); in SS (59.6%) and RP (64.7%) the most fequent species was A. veniliae, followed in SS by A. aﬀ. negro (14.9%) and in RP by A. leucogramma (13.5%). The size of reproductive niches, H’=1.25 (IS),H’=1.30 (SS) and H’=1.29 (RP) were not significantly different. There was a positive correlation between the reproductive niche width (H’) and evenness.